Pregnant women infected with pandemic influenza A(H1N1)pdm09 virus showed differential immune response correlated with disease severity - Periolo, Natalia (2015)
Fil: Periolo, Natalia. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Virología. Servicio de Virosis Respiratoria. Laboratorio Nacional de Referencia de Influenza y Virus Respiratorios. National Influenza Centre PAHO/WHO; Argentina.